Ca–Ag compounds in ethylene epoxidation reaction. Issue 1 (31st December 2019) - Antonyshyn, Iryna; Sichevych, Olga; Ormeci, Alim; Burkhardt, Ulrich; Rasim, Karsten; Titlbach, Sven; Armbrüster, Marc; Schunk, Stephan A.; Grin, Yuri
ABSTRACT: The ethylene epoxidation is a challenging catalytic process, and development of active and selective catalyst requires profound understanding of its chemical behaviour under reaction conditions. The systematic study on intermetallic compounds in the Ca–Ag system under ethylene epoxidation conditions clearly shows that the character of the oxidation processes on the surface originates from the atomic interactions in the pristine compound. The Ag-rich compounds Ca2 Ag7 and CaAg2 undergo oxidation towards fcc Ag and a complex Ca-based support, whereas equiatomic CaAg and the Ca-rich compounds Ca5 Ag3 and Ca3 Ag in bulk remain stable under harsh ethylene epoxidation conditions. For the latter presence of water vapour in the gas stream leads to noticeable corrosion. Combining the experimental results with the chemical bonding analysis and first-principles calculations, the relationships among the chemical nature of the compounds, their reactivity and catalytic performance towards epoxidation of ethylene are investigated. GRAPHICAL ABSTRACT: uf0001